LIFE CYCLE ASSESSMENT SEPEDA MOTOR DI INDONESIA - SETIOWATI, SETIOWATI; Sopha, Bertha Maya ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The alarming rate of air pollution causes a global concern. In Indonesia, the pollution itself is mainly caused from transportation byproducts with a rate of 70% share with 81% operating vehicles share came from motorcycles. The rate increases between 9% to 26% each year and affects significantly both direct and indirect to the environment. This situation calls for a suitable method of assessing and measuring the portion of the effect to the environment. The assessed aspects should include the products, manufacturing process, and also its life span usage and it will be called Life Cycle Assessment (LCA). This study is aimed at analyzing LCA on the matter of energy consumption and environmental impact of a motorcycle product with a life cycle perspective. The areas of the study are the manufacturing process and infrastructure of the building, operation and fuel extraction, maintenance, and disposal phase. The functional unit of measurement is one passenger per kilometer (pkm). Database is compiled from observation, interview, ecoinvent data, and other means of supporting empirical data. The result showed that motorcycle usage on a functional unit will contribute to Abiotic resource Depletion Potential (ADP) in amount of 4,31E-14 kg Sbeqv, Global Warming Potential (GWP) in amount of 4,67E-01 kg CO2eqv, Human Toxicity Potential (HTP) in amount of 3,58E-01 kg 1,4-DCBeqv, Acidification Potential (AP) in amount of 7,10E-04 kg SO2eqv, Ecotoxicity Potential (Eco) for emission to air in amount of 1,15E-03 kg 1,4-DCBeqv, Photochemical Ozone Creation Potential (POCP) in amount of 4,39E-04 kg ethyleneeqv, Ozone Depletion Potential (ODP) in amount of 2,94E-05 kg CFC-11eqv, and Eutrophication Potential (EP) in amount of 8,78E-05 kg PO3-2eqv. In this matter, manufacturing and operation process are the largest contributor. To cope with this matter, several steps can be undertaken to reduce the environmental effect, for instance, by manufacturing process revamp, or greener fuel choice.